90.8k views
3 votes
What is -5 1/2 - 4 1/4 + 6 3/4=​

User Karbi
by
4.9k points

2 Answers

5 votes

Answer:

-3

Explanation:


-5(1)/(2) -
4(1)/(4) + 6
(3)/(4)

Writing the equation in improper function we get;


-(11)/(2) -
(17)/(4) +
(27)/(4) =
(-22 - 17 + 27)/(4) = (-12)/(4) = -3

User Art Spasky
by
5.1k points
4 votes

Answer:

-3

Explanation:

Given that:


-5(1)/(2)-4(1)/(4)+6(3)/(4)

Converting in to a proper fraction, we get:


-(11)/(2)-(17)/(4)+(27)/(4)

Multiplying and dividing the first fraction by two to make the fraction consistent.

=>
-(11*2)/(2*2)-(17)/(4)+(27)/(4)

=>
-(22)/(4)-(17)/(4)+(27)/(4)

=>
(-22-17+27)/(4)

=>
-(12)/(4)

=> -3

Therefore, the final solution is -3.

User Krzysztof Cieslak
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.